Using Canva For Education to Improve the Skills of Physics Teachers in Pesisir Selatan in Developing Innovative Learning Media - Riyasni, Selma; Chairani, Vici Syahril (Fakultas MIPA Universitas Negeri Padang, 2024)
Abstract – The use of ICT in learning today is a very important thing. Teachers are required to be able to develop learning media and create ICT-based learning resources. One problem in the Physics MGMP of Pesisir Selatan Regency is the lack of understanding in creating ICT-based learning media and learning resources. The government, through the Belajar.id account has provided Canva Premium access to teachers, education staff, and even students to access Canva Premium accounts with the Canva for Education program. Implementing technical guidance for creating learning media using a Canva for Education account can increase teachers' knowledge and skills in creating innovative learning media. The results of the implementation of technical guidance have positively impacted teachers at MGMP Pesisir Selatan Regency in developing innovative learning media.